Spontaneous Rupture of Extensor Pollicis Longus Tendon: Clinical and Occupational Implications, Treatment Approaches and Prognostic Outcome in Non-Rheumatoid Arthritis Patients: A Retrospective Study - Al-Omari AA (Dove Medical Press, 2020)
Ali A Al-Omari,1 Anas AR Altamimi,2 Esra’a ALQuran,3 Abed Allah Ahmad Saleh,1 Qusai Mustafa Alyafawee,1 Mohammad Ziad Audat,4 Khaldoon Bashaireh1 1Department of Special Surgery, Division of Orthopedics, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Department of General and Specialized Surgery, Faculty of Medicine, Hashemite University, Zarqa 13133, Jordan; 3Department of Pathology, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, Jordan; 4King Abdullah University Hospital, Jordan University of Science and Technology, Irbid 22110, JordanCorrespondence: Ali A Al-OmariDepartment of Special Surgery, Division of Orthopedics, Faculty of Medicine, Jordan University of Science and Technology, P. O. Box: 3030, Irbid 22110, JordanTel +962 796903766Fax +962 2 7201064Email dr.ali.omari80@gmail.comBackground: Spontaneous rupture of extensor pollicis longus (EPL) tendon is a rare condition often found in patients actively having regular extensive use of hands and fingers especially the thumb. In this article, we report 7 cases of spontaneous rupture of EPL tendon and investigate the associated factors and treatment outcome.Methods: Retrospectively, the databases for the 7 cases were retrieved and studied. These cases represent all cases of spontaneous rupture of EPL in our institution. Demographic data, clinical presentation, any history of trauma or steroid injection, laboratory and clinical findings suggestive for rheumatoid arthritis, co-morbidities and imaging findings were obtained. In addition, the operative technique and findings were retrieved. Moreover, histopathological studies and follow-up assessment were included.Results: Six males and one female were included. The mean age was 45.2 years. No prior history of trauma, rheumatological disease or steroid use was detected in any patient. All patients experienced prodromal pain in the radial side. Clinical examination was the most effective diagnostic measure. Magnetic resonance imaging (MRI) was used to confirm the diagnosis and to look for other abnormalities that may predispose to rupture. Five patients underwent extensor indicis proprius to EPL tendon transfer employing Pulvertaft weave technique and one patient underwent primary repair as there was a little gap in the tendon ends. In this study, one patient refused any treatment. All patients achieved a favorable outcome at the last follow-up.Conclusion: Diagnosis of spontaneous ruptures of EPL tendon can be confirmed through clinical examination and MRI for patients with restricted thumb movement even with the absence of any identifiable predisposing risk factor. During surgery, detailed attention must be drawn towards the tendon ends which can have unusual gaps and bone abnormalities.Keywords: thumb, interphalangeal joint, rheumatoid arthritis, tendon, extensor pollicis longus